2018
DOI: 10.1111/jth.13897
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and quality of oral anticoagulation treatment in pediatric patients in the Netherlands based on the CAPS cohort

Abstract: To cite this article: Maagdenberg H, Bierings MB, van Ommen CH, van der Meer FJM, Appel IM, Tamminga RYJ, de Boer A, Maitland-van der Zee AH. Characteristics and quality of oral anticoagulation treatment in pediatric patients in the Netherlands based on the CAPS cohort. 2018; 16: 116-24. J Thromb Haemost Essentials• The knowledge of quality and safety of acenocoumarol and phenprocoumon use in children is limited.• We used data from a multicenter retrospective followup study in children in the Netherlands.• The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The doses recommended in the guidelines seem to be safe, but are not yet optimal, with percentages of time in which the INR is within the therapeutic range (time in therapeutic range [TTR]) of around⁓ 50% during the first year of treatment . Within the cohort of the Children Anticoagulation and Pharmacogenetics Study, we obtained similar results within the first 3 months of acenocoumarol use (54.6%), and higher percentages after the first 3 months of use (> 64%) .…”
Section: Introductionsupporting
confidence: 51%
“…The doses recommended in the guidelines seem to be safe, but are not yet optimal, with percentages of time in which the INR is within the therapeutic range (time in therapeutic range [TTR]) of around⁓ 50% during the first year of treatment . Within the cohort of the Children Anticoagulation and Pharmacogenetics Study, we obtained similar results within the first 3 months of acenocoumarol use (54.6%), and higher percentages after the first 3 months of use (> 64%) .…”
Section: Introductionsupporting
confidence: 51%
“…One study found the lowest TTR for target INR range of 2.0-2.5 (30%, p < .001). 35 Another study's lowest TTR was for INR target 2.5-4.0 (p = .006), 21 while the lowest TTR for the other study was for goal INR of 2.0-3.0 (p = .002). 27 Additionally, one study reported that TTR was negatively correlated with the number of INR measurements obtained in the first 9 months of therapy, as well as the number of dose adjustments in the first 12 months of therapy (p < .05).…”
Section: Treatment Characteristicsmentioning
confidence: 91%
“…Characteristics of the 17 included studies are shown in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Seven studies collected data prospectively and the remaining 10 collected data via retrospective medical record reviews. Mean ages of the patient populations ranged from 3.7 to 14.2 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations